Enhancing Distance Learning Through Client-Server-Based Learning Media in Object-Oriented Programming Education - Hadid Putri B. Zurna; Mukhlidi Muskhir; Dedy Irfan; M Giatman (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop and test the effectiveness of client-server-based learning media for Object-Oriented Programming courses in the Informatics Study Program at PGRI University of West Sumatra. The research employed the Research and Development method with the ADDIE model. Validation was conducted by media and material experts, with media validation reaching 77.55% (valid category) and material validation 83.90% (highly valid category). Practicality testing by lecturers showed a practicality level of 87.00% and by students 86.31% (very practical category). Learning effectiveness was measured through learning outcome tests with a classical completeness rate of 96.67% and an N-Gain value of 0.687 (medium category). The results indicate that the developed client-server-based learning media is valid, practical, and effective for distance learning in Object-Oriented Programming courses.